The Moderating Role of Firm Value on the Relationship between Financial Ratios and Technology Stock Prices in the Indonesian Sharia Market - didi; Peny Cahaya Azwari; Chandra Zaki Maulana (LP2M IAIN Palopo, 2026)
This study investigates the influence of Price Earning Ratio (PER) and Price to Book Value (PBV) on sharia stock prices within the technology sector, while also examining the moderating role of firm value, proxied by Tobin's Q. The research focuses on companies consistently listed in the Indonesian Sharia Stock Index (ISSI) during the 2020-2024 period. A quantitative causal-associative approach was employed using panel data regression with a Fixed Effect Model (FEM) on ten technology companies that met the purposive sampling criteria. The findings reveal that both PER and PBV have a positive and significant direct effect on sharia stock prices. However, firm value only significantly moderates the relationship between PBV and stock prices, acting as a negative moderator that weakens PBV's influence when firm value is high. The model demonstrates exceptional explanatory power with an Adjusted R-squared value of 98.03 percent. This research contributes empirical evidence to signaling theory within the Islamic capital market context and provides practical guidance for sharia investors suggesting a combined analysis of PBV and firm value rather than relying solely on single indicators for investment decisions in the technology sector.